Tumor Reduction in Multiple Myeloma: New Concepts for New Therapeutics - Alonso, Rafael; Lahuerta, Juan José (Frontiers in Oncology, 2022)
The development of new resources for a more accurate diagnosis and response assessment in multiple myeloma has been a long process along decades, mainly since the middle of 20th century. During this time, the succession of technical advances has run parallel to the better knowledge of the disease biology and the availability of novel therapeutic strategies. The cornerstone of standardized criteria to uniformly evaluate the disease response in myeloma dates back to the 1990s when the key role of complete remission was established. Since then, different updates have been implemented according to available scientific evidences not always without certain controversies. The progressive improvements in survival results of myeloma patients and the growing quality of responses due to the novel therapies has led to the need of developing new tools for a better monitoring of tumor burden. In this way, the concept of minimal residual disease and its key value based on the prognostic significance and the clinical relevance has been consolidated during the last years, overcoming the value of conventional response criteria or classical adverse prognosis markers. Nevertheless, its precise role in the clinical management of myeloma patients to detect early treatment failure and trigger early rescue strategies is still pending to be defined. In this review we revisit the major milestones in the understanding of tumor reduction in multiple myeloma until the most recent imaging techniques or liquid biopsy approaches, including a critical view of conventional response criteria whose backbone has remained unchanged during the last 20 years.